Global Financial Stability Report, September 2005 : Financial Stability Considerations Related to Trends in Accounting Standards. (Global Financial Stability Report; Global Financial Stability Report ;, 2005)
This paper describes financial stability considerations related to trends in accounting standards. The paper highlights that in recent years, financial stability is generally viewed by authorities as having improved, in large part through more proactive risk management activities by banks and the related transfer and dispersion of risks from banks to diverse nonbanking institutions, which often have longer-term liability structures. This paper presents a balanced review of the relevant policy issues, and raises questions related to financial stability that policymakers may consider as accounting standards are being reviewed.